Direct On Line Circuit as a 3 Phase Motor Controller Using the Siemens S7 1200 Programmable Logic Controller - Sherlly Dwi Anggrainy; Haris Abizar; Jan Manendro Budi Utomo (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
In today's world of education, teachers are required to be creative in the teaching process. Teachers are very influential in the development of education in Indonesia. One indicator of a country's progress can be seen from education. This research uses descriptive experimental research that uses a qualitative approach. This research is descriptive because this research does not use a particular method but only uses existing facts and is temporary. The DOL Circuit System is used in three-phase induction motor starting systems and is designed to minimize very high starting current surges. The three-phase induction motor starter system with the DOL circuit works directly to provide 380 VAC voltage to the motor coil so that the motor rotates immediately. The first condition is when the MCB is activated the L2 lamp output immediately activates as a sign that the DOL circuit is on standby. Then the second condition describes the circuit when the MCB is active and S2 is pressed, K1 will be active so that the resulting output is L3 on. Entering the third condition shows that the MCB remains active and S1 is pressed, the output that occurs is L2 lights up. The fourth condition where the MCB remains on then EMG is activated, the output that occurs is L4 lights up. In the fifth condition, the MCB remains on and the TOR is activated, so that the outputs, namely L1 and L2, light up simultaneously.